Contemporary economics : an applications approach - Carbaugh, Robert J., 1946- (Cincinnati OH : South-Western College, 2001)
Introduction. The microeconomy. The macroeconomy. The international economy.
Keywords: Economics; Unites States; Economics; United States -- Economic conditions